Manually mapped retrogressive thaw slumps in West Siberia, version 0.1 - Nina Nesterova; Ilya Tarasevich; Marina Leibman; Artem V Khomutov; Alexander Kizyakov; Ingmar Nitze; Guido Grosse (PANGAEA, 2025)
This dataset presents a comprehensive update to the inventory of retrogressive thaw slumps (RTS) in northern West Siberia, achieved through meticulous manual mapping. RTS sites were identified using high-resolution satellite basemaps from ESRI, Google Earth, and Yandex Maps, spanning multiple years and sources. The dataset includes both newly mapped locations and previously reported RTS occurrences from existing literature, allowing for a consolidated view of RTS distribution in the region. The collected data underwent rigorous manual filtering and verification, leveraging local field experience and observations from key sites to reduce uncertainty and minimize false positives. Each RTS is characterized according to a classification system that accounts for key environmental parameters, including morphology, spatial organization, terrain position, and associated geomorphic processes. This work enhances the understanding of RTS distribution and characteristics in West Siberia, offering valuable insights into regional landscape dynamics and environmental change.